2020
DOI: 10.1186/s12939-020-01212-5
|View full text |Cite
|
Sign up to set email alerts
|

Extent of and trends in inequalities in child stunting in Sierra-Leone from 2005 to 2013: evidence from demographic and health surveys and multiple indicator cluster surveys

Abstract: Background: Comprehensive assessment of stunting disparity in Sierra-Leone has not been done so far. We aimed to document extent and over time dynamics of inequality in stunting in Sierra-Leone using approaches that facilitate implementation of interventions aim to eliminate non-justified stunting disparity in the country. Methods: The data for the study were derived from two rounds of the Sierra Leone Demographic and Health Survey conducted in 2008 and 2013, and two rounds of the Sierra Leone Multiple Indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 26 publications
(32 reference statements)
3
14
1
Order By: Relevance
“…Consistent with previous studies conducted in Nepal [23], Nigeria [20], and Sierra Leone [21], our ndings showed that inequalities in childhood stunting were prevalent among children from the poorest wealth categories. The plausible reason could be that people in the poorest wealth quantile may encounter nancial challenges in their attempt to access nutritious foods for their children, and this may increase the likelihood of stunting in their children.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous studies conducted in Nepal [23], Nigeria [20], and Sierra Leone [21], our ndings showed that inequalities in childhood stunting were prevalent among children from the poorest wealth categories. The plausible reason could be that people in the poorest wealth quantile may encounter nancial challenges in their attempt to access nutritious foods for their children, and this may increase the likelihood of stunting in their children.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, our nding showed sex-related stunting inequality favouring female children. This nding is congruent with previous studies conducted in Nigeria [20], Senegal [25], and Sierra Leone [21] that demonstrated that female children have lower odds of experiencing stunting than their male counterparts. The simple measures indicated a signi cant disparity in stunting at the detriment of male children throughout the period studied.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“… 4 Stunting is one of the manifestation of undernutrition and a preferred anthropometric measure for the assessment of chronic nutritional status. 5 , 6 A child is considered stunted when he/she has z -score value for height-for-age below minus 2 standard deviations (−2SD) from the median of the World Health Organization (WHO) standard growth charts. 7 Stunting is considered as “best overall indicator” of children’s well-being and an “accurate reflection” of disparities among populations.…”
Section: Introductionmentioning
confidence: 99%
“…21 , 22 However, Sierra Leone is far from achieving this having had a meager average annual reduction of only 0.25% between 2005 and 2013. 5 Studies based on national and regional data from the country have shown stark inequalities in stunting prevalence across regions, residence, and socio-economic status. 5 While wealth and educational inequalities have been shown to have slightly improved over time, residence (rural and urban) and subnational regional inequalities have remained unchanged.…”
Section: Introductionmentioning
confidence: 99%